The health-promoting experiences of storytellers in group-based digital storytelling workshops: a meta-synthesis of qualitative studies - Dominguez Hernandez, Jonathan; Brieskorn, Bernadette Irene; Leutenegger, Vanessa; Krahl, Astrid; Eastham, Rachael; Limmer, Mark (Frontiers in Digital Health, 2025)
ObjectiveTo synthesize qualitative evidence, using the framework analysis method, on how participating in a digital storytelling workshop shapes the storytellers’ health attitudes, values, beliefs, or behaviors.MethodsWe conducted a meta-synthesis using the framework analysis method to generate analytic themes. We searched Medline, CINHAL, SocIndex, Embase, PsycINFO, SciELO, Academic Search Ultimate, Scopus, the Directory of Open Access Journals, and LIVIVO. We used the GRADE-CERQual approach to assess the confidence in the review findings.ResultsWe included 25 qualitative studies from six countries representing the experiences of 629 storytellers. Confidence in most review findings was moderate. Storytellers experience digital storytelling workshops as a safe space where they reframe the narratives around their health experiences. This re-storying process extends storytellers’ understanding of their health experiences, affords them a sense of agency and control, and motivates them to use their stories to support others.ConclusionWe found evidence that digital storytelling enables storytellers to reflect and emotionally engage with the narratives shared in the co-construction of digital stories, resulting in a narrative shift that is likely to be experienced as health-promoting.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42023478062, PROSPERO CRD42023478062.